Towards the Efficiency of the Ratio Estimator for Population Median in Survey Sampling (Global Journal of Science Frontier Research, 2021)
This study leveraged on the fact that researchers in survey sampling sometimes do not take into consideration the tool that will be most appropriate in the measure of location. As a result, users of statistics often go for the mean or total, which has been widely discussed in the finite population sampling literature, unlike the median, which is more complicated to deal with given that it has to do with ordered data. This study suggests an estimator of population median in single and double sampling technique with two auxiliary variables. From the result obtained, it is established that the proposed estimators perform better when the considered variables are from a highly skewed distribution, such as income, expenditure, scores. In addition, it was observed that the proposed estimators were less bias and more efficient than the existing estimators of their class.